Bone mineral density parameters and related nutritional factors in vegans, lacto-ovo-vegetarians, and omnivores: a cross-sectional study - Galchenko, Alexey; Rizzo, Gianluca; Sidorova, Elizaveta; Skliar, Elena; Baroni, Luciana; Visaggi, Pierfrancesco; Guidi, Giada; de Bortoli, Nicola (Frontiers in Nutrition, 2024)
The growing prevalence of vegetarianism determines the need for comprehensive study of the impact of these diets on health and particularly on bone metabolism. We hypothesized that significant dietary differences between vegans, lacto-ovo-vegetarians, and omnivores also cause significant differences in their nutrient status, which may affect bone health. The study assessed dual-energy X-ray absorptiometry parameters in lumbar spine and femoral neck, average nutrient intake, serum nutrient concentrations, serum PTH levels, and urinary pH among 46 vegans, 38 lacto-ovo-vegetarians, and 44 omnivores. There were no differences in bone mineral density (BMD) between the groups. However, the parathyroid hormone (PTH) levels were still higher in vegans compared to omnivores, despite the same prevalence of hyperparathyroidism in all groups. These findings may probably be explained by the fact that each group had its own "strengths and weaknesses". Thus, vegans and, to a lesser extent, lacto-ovo-vegetarians consumed much more potassium, magnesium, copper, manganese, and vitamins B6, B9, and C. At the same time, the diet of omnivores contained more protein and vitamins D and B12. All the subjects consumed less vitamin D than recommended. More than half of vegans and omnivores had insufficiency or even deficiency of vitamin D in the blood. Low serum concentrations of manganese with its quite adequate intake are also noteworthy: its deficiency was observed in 57% of vegans, 79% of lacto-ovo-vegetarians, and 63% of omnivores. Currently, it is no longer possible to conclude that lacto-ovo-vegetarians have lower BMD than omnivores, as our research supported. Vegans in our study also did not demonstrate lower BMD values, only higher PTH blood concentrations, compared to omnivores, however, a large number of studies, including recent, show the opposite view. In this regard, further large-scale research is required. Vegans and lacto-ovo-vegetarians now have a variety of foods fortified with vitamins D and B12, as well as calcium. There is also a great diversity of ethically sourced dietary supplements. The found low concentrations of manganese require further investigation.